Neutron diffraction and gravimetric study of the iron nitriding reaction under ammonia decomposition conditions - Wood, T; Makepeace, J; David, W (Royal Society of Chemistry, 2017)
Ammonia decomposition over iron catalysts is known to be affected by whether the iron exists in elemental form or as a nitride. In situ neutron diffraction studies with simultaneous gravimetric analysis were performed on the nitriding and denitriding reactions of iron under ammonia decomposition conditions. The gravimetric analysis agrees well with the Rietveld analysis of the neutron diffraction data, both of which confirm that the form of the iron catalyst is strongly dependent on ammonia decomposition conditions. Use of ammonia with natural isotopic abundance as the nitriding agent means that the incoherent neutron scattering of any hydrogen within the gases present is able to be correlated to how much ammonia had decomposed. This novel analysis reveals that the nitriding of the iron occurred at exactly the same temperature as ammonia decomposition started. The iron nitriding and denitriding reactions are shown to be related to steps that take place during ammonia decomposition and the optimum conditions for ammonia decomposition over iron catalysts are discussed.